(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This study aims to develop smartphone-based interactive multimedia products using smart apps creator (SAC) which was developed through the development of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The product developed was tested based on the criteria of validity, practicality, and effectiveness of its use for learning mathematics. The research subjects were teachers and students of class X IPA 1 Public senior high school 4 Gorontalo as many as 28 students. The product is considered suitable for use based on the validity criteria from the assessment of the material expert, an average score of 3.45 is obtained in the very appropriate category, the media expert assessment is obtained by an average score of 3.78 in the very appropriate category, and the assessment of the learning design expert obtains an average score of 3.76 in the very category. worthy. Based on the practicality of the product, it is considered feasible to use with an average percentage of student responses of 84.29% in the practical category, and the average teacher response of 95.8% in the very practical category. The product is also considered effective as seen from the pretest and posttest scores obtained a gain score of 0.62 in the medium category